Penegakan Hukum Tilang Elektronik (ETLE) terhadap Pelanggaran Lalu Lintas di Kota Pekanbaru - Muhammad Ihcsan; Siti Rahmah; Feni Puspitasari (MAN 4 Kota Pekanbaru, 2026)
This study aims to examine the implementation of Electronic Traffic Law Enforcement (ETLE) in Pekanbaru City and to identify the obstacles faced by the Law Enforcement Sub-Directorate (Subdit Gakkum) of the Riau Regional Police Traffic Directorate in its implementation. This research employed an empirical legal research method with a sociological approach. Data were collected through interviews, observations, and library research, and were analyzed using a qualitative descriptive method. The results indicate that the implementation of ETLE in Pekanbaru has generally been effective in improving legal certainty, transparency, and public compliance with traffic regulations. However, several obstacles remain, including limited facilities and infrastructure, inadequate human resources, inaccurate vehicle registration data, low public legal awareness, and limited operational funding. Therefore, improving infrastructure, human resources, and public education is essential to optimize the implementation of ETLE.